THE ROLE OF PERCEIVED SUPERVISOR SUPPORT ON LOYALTY AND PERFORMANCE OF KSP ARTHA MULIA YOGYAKARTA EMPLOYEES (International Conference on Economics, Business, and Management Research (ICEBMR), 2024)
Improving employee performance is always a concern because of its ongoing impact on the overall performance of the organization. The role of supervisor support is considered crucial in building worker loyalty. The presence of loyal workers is expected to contribute to the improvement of organizational achievements. This study aims to determine the impact of perceived supervisor support on employee performance through the mediation of job loyalty at KSP Artha Mulia Yogyakarta. A total of 36 respondents were involved in this survey, whose data were taken by census using a questionnaire instrument. This research is quantitative, with multiple linear regression data analysis and sobel test. The results showed no significant direct effect of perceived supervisor support on employee performance. Perceived supervisor support has a significant effect on employee loyalty, but loyalty was not found to affect performance. Thus, the influence of supervisor support on performance through job loyalty was not confirmed. Supporting supervisors who have concern for the psychological and economic well-being of subordinates can be done by organizations when they want to maintain the loyalty of their workers.
Keywords: employee performance; perceived supervisor support; work loyalty